The Main Issues of the Study of Kinship and Kin Groups of Contemporary Tuvans: Passportization, Terminology and Maintenance of Kinship - Lamazhaa, Chimiza K. (The New Research of Tuva, 2021)
The article highlights and analyzes three main problematic nodes of the anthropology of kinship among the Tuvans: the passportization of the 1940s and Tuvan anthroponymy, the terminology of kinship; contemporary kinship relations and ties of the Tuvans. It is noted that today the study of these topics is especially significant because of the actualization of kinship issues among modern Tuvans. Thus, it is necessary to carry out research within an interdisciplinary synthesis of different humanities disciplines.The passportization of the 1940s in Tuva has hardly been studied by historians. Consequently, the author draws attention to the key milestones of these events and specifies the relevant documents. It is important to consider the events and consequences in Tuva, taking into account the general principles of the Soviet passportization process. It is argued that the Soviet version of social engineering, designed to keep records of the population, led to certain changes in the kinship system of many Tuvans. Having different surnames and patronymics, kindred people were alienated from each other, but the consequences of this were revealed only many years later. Over time the ties between relatives were being lost, and many descendants do not know the ancestors of direct and immediate kinship at all, they are not even familiar with blood relatives of the extended family.An analysis of the second theme in literature and a terminological review of the words the Tuvans use today to denote common kinship and groups of relatives show that the main terms are tөrel aimag, tөrel bөluk, and tөrel-dөrgul. Accordingly, in Russian it is more properly to discuss contemporary Tuvan social communities that have kin relations using the term “kin group” rather than “tribal group”.The loss of the Tuvan kinship system in the 20th century and changes in relations have led to the fact that today the very maintenance of family ties becomes a problem for kin groups of the Tuvans. In order to preserve and develop ties, special efforts must be undertaken. In the author’s opinion, this process is interesting to study with the help of such an anthropological approach as kin keeping, i.e. the ‘preservation of kinship’. We see that the Tuvans have a kind of kinkeepers — organizers of kinship gatherings and rituals. These kinkeepers have become mediators between nuclear families and an extended family — a kinship group.
Keywords: Tuvans; kinship; kinship system; kin group; ethnic terminology; kinship terminology; passportization; anthroponymy; preservation of kinship; kinkipper; contemporary ritualism